2016
DOI: 10.1007/s40256-016-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine: A Review of Labeled and Off-Label Uses

Abstract: Ivabradine is a unique medication recently approved in the USA for the treatment of select heart failure patients. It was first approved for use in several countries around the world over a decade ago as an anti-anginal agent, with subsequent approval for use in heart failure patients. Since ivabradine has selective activity blocking the I f currents in the sinus node, it can reduce heart rate without appreciable effects on blood pressure. Given this heart-rate-specific effect, it has been investigated in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
0
19
0
3
Order By: Relevance
“…While previous research [50] did show improvements in clinical outcome (cardiovascular death or hospital admission for worsening of heart failure) in patients with heart failure after HR reduction with Ivabradine, a recent study in patients with stable coronary disease without clinical heart failure [51], showed that additional treatment with Ivabradine did not lead to a reduction in cardiovascular death or nonfatal myocardial infarctions. Therefore, it is of great interest to further investigate which patient groups may and may not benefit from HR lowering treatment with Ivabradine [52, 53]. In the present study, the animals’ HR was measured once before the MR and US examinations performed after 14 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…While previous research [50] did show improvements in clinical outcome (cardiovascular death or hospital admission for worsening of heart failure) in patients with heart failure after HR reduction with Ivabradine, a recent study in patients with stable coronary disease without clinical heart failure [51], showed that additional treatment with Ivabradine did not lead to a reduction in cardiovascular death or nonfatal myocardial infarctions. Therefore, it is of great interest to further investigate which patient groups may and may not benefit from HR lowering treatment with Ivabradine [52, 53]. In the present study, the animals’ HR was measured once before the MR and US examinations performed after 14 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition leads to reduction of the slow depolarization action potential and thereby resulting in decreased heart rate. As far as known, ivabradine does not directly modify other cardiovascular parameters and, therefore, will not cause reduction of blood pressure, in contrast to β-blockers [78,79].…”
Section: Ivabradinementioning
confidence: 97%
“…A szelektív I f -csatorna-inhibitor gyógyszer, az ivabradin minden esetben hatékony volt. Az alkalmazott adagban, más bradycardizáló gyógyszert együtt nem használva, mellékhatást, intoleranciát nem észleltünk (14)(15)(16)(17). A familiáris IST hátterében számos kiváltó ok már régóta felmerült: a sinuscsomó pacemaker-sejtjeinek fokozott aktivitása/érzékenysége, fokozott szimpatikus szenzitivitás, csökkent vagalis tónus mellett aktiváló-dalom, pszichés feszültség is felmerült.…”
Section: Megbeszélésunclassified